2016
DOI: 10.1007/s00394-016-1250-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to sugary drinks in humans: galactose presents milder cardiac effects than glucose or fructose

Abstract: 1Conclusions Galactose thus presents the interesting characteristics of a low-glycemic sugar with mild cardiovascular effects. Further studies are warranted to confirm the clinical relevance of the milder cardiovascular effects of galactose than other sugars for insulin resistant obese and/ or diabetic patients with cardiac insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Reduced adult adiposity observed in GLU + GAL–fed females might be due to differential effects on insulin signaling. The insulin response provoked by galactose (considering the direct effect) was small when compared with that of glucose [summarized in (35)]. Moreover, galactose has been reported to improve insulin sensitivity in rats (36).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced adult adiposity observed in GLU + GAL–fed females might be due to differential effects on insulin signaling. The insulin response provoked by galactose (considering the direct effect) was small when compared with that of glucose [summarized in (35)]. Moreover, galactose has been reported to improve insulin sensitivity in rats (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lactose is a disaccharide comprising of the monosaccharides glucose and galactose, at which galactose has received much attention as a low-glycemic index sugar, with only small increases in plasma glucose and insulin in response to its ingestion (46,75,76). Recently, the cardiovascular effects of galactose have also been explored (77). In this context, acute cardiovascular responses to the ingestion of 60 g galactose were investigated and compared with the same quantity of fructose or glucose with the use of a randomized crossover study design (77).…”
Section: Galactosementioning
confidence: 99%
“…Recently, the cardiovascular effects of galactose have also been explored (77). In this context, acute cardiovascular responses to the ingestion of 60 g galactose were investigated and compared with the same quantity of fructose or glucose with the use of a randomized crossover study design (77). This study observed that glucose and galactose had minor effects on blood pressure, which contrasted to the blood-pressure-elevating effect of fructose.…”
Section: Galactosementioning
confidence: 99%
“…In healthy older participants [11,12,46] and patients with T2DM [11,64], the fall in BP following glucose ingestion has been shown to be related to the rate of gastric emptying of glucose, i.e., faster gastric emptying is associated with a greater fall in BP. In contrast, in healthy young participants, there is little fall, and in some cases an increase in, SBP following oral glucose [53,89]. The fall in postprandial BP appears to be on a continuum so that with increasing age, the fall in BP is greater.…”
Section: Nutritive Sweetenersmentioning
confidence: 99%
“…Compared with glucose, fructose is absorbed more slowly from the intestine [100,101]. There has been a total of five studies relating to the effects of oral fructose on postprandial BP in a range of cohorts including in healthy participants [39,40,41,50,89] and hypertensive patients [41] (Table 2).…”
Section: Nutritive Sweetenersmentioning
confidence: 99%